Comparative Evaluation of Echinococcus Serology with Cytology for the Diagnosis of Hepatic Hydatid Disease - Mahajan, Supriya; Thapar, Shalini; Khillan, Vikas; Gupta, Pradheer; Rastogi, Archana; Gupta, Ekta (Journal of Laboratory Physicians, 2020)
Objectives The purpose of this study is to determine the diagnostic efficacy of enzyme-linked immunosorbent assay (ELISA) in radiologically confirmed liver mass lesions for the diagnosis of hepatic hydatid disease (HHD) and to compare the diagnostic performance of ELISA with fine needle aspiration cytology (FNAC) (taken as standard) for HHD diagnosis.Materials and Methods This retrospective study included blood samples of 223 patients with radiologically confirmed liver mass lesions in which immunoglobulin G (IgG) anti-Echinococcus antibodies were tested using a commercial IgG ELISA (RIDASCREEN, R-Biopharm AG, Darmstadt, Germany). Results of ELISA, ultrasonography, FNAC, and liver function tests were obtained from the hospital information system. ELISA results were compared with those of FNAC to analyze the diagnostic efficacy of ELISA for HHD diagnosis.Statistical Analysis Comparison of the results obtained from ELISA was performed with respect to FNAC results (taken as standard) to analyze the diagnostic efficacy of ELISA for HHD detection. Data has been represented as median (range) or in frequencies. Wilson score was used to assess 95% confidence interval of diagnostic parameters. The analysis was performed using SPSS Version 22.0 (IBM Corp.) and Open Epi (version 3.01).Results Out of 223 cases with liver mass lesions, Echinococcus IgG was reactive in 62 (28%) cases and FNAC was positive in 16 (7.2%) cases. Since two cases were FNAC-positive but IgG-nonreactive, total HHD cases were 64 (28.7%). Echinococcus IgG reactive cases were seen more in the extremes of age group, that is, 1 to 10 years and 81 to 90 years. Taking FNAC as the standard, the sensitivity, specificity, positive predictive value, and negative predictive value of ELISA were 87.5, 76.8, 22.6, and 98.7%, respectively. Cytology-positive cases demonstrated a mean ELISA optical density/cut-off (OD/CO) of 4.2 ± 3 standard deviation.Conclusion ELISA in radiologically confirmed liver mass cases is highly sensitive in detecting HHD and hence should be used along with ultrasonography for the screening of HHD followed by confirmation with cytology even in cases with a higher OD/CO of ELISA.
Keywords: hepatic hydatid disease; ELISA; fine needle aspiration cytology; liver mass lesions